Data mining concepts and techniques - Han, Jiawei (Morgan Kaufmann, 2012)
Equips you with an understanding and application of the theory and practice of discovering patterns hidden in large data sets. This title focuses on important topics in the field: data warehouses and data cube technology, mining stream, mining social networks, and mining spatial, multimedia and other complex data.